Deer antler stem cells immortalization by modulation of hTERT and the small extracellular vesicles characters - Chen, Ze; Meng, Deshuang; Pang, Xin; Guo, Jia; Li, Tiejun; Song, Jun; Peng, Yinghua (Frontiers in Veterinary Science, 2024)
BackgroundDeer antler stem cells (AnSCs) exhibit properties of both embryonic and mesenchymal stem cells, with superior self-renewal and proliferation, which drive rapid antler growth and regeneration. AnSCs and their derived small extracellular vesicles (sEVs) hold promising potential for applications in regeneration medicine. Due to the restricted proliferative capacity inherent in primary cells, the production capacity of AnSCs and their sEVs are limited. Human telomerase reverse transcriptase (hTERT) is the most important telomerase subunit, hTERT gene insertion has been successfully employed in generating immortalized cell lines.ResultsIn this study, we successfully established immortalized AnSCs by transducing the hTERT gene using lentivirus. Compared to primary AnSCs, hTERT-AnSCs demonstrated extended passage potential and accelerated proliferation rates while maintaining the mesenchymal stem cell surface markers CD44 and CD90. Additionally, hTERT-AnSCs retained the capacity for osteogenic, adipogenic, and chondrogenic differentiation. sEVs derived from hTERT-AnSCs exhibited a particle size distribution similar to that of AnSCs, both displaying a cup-shaped morphology and expressing CD81, ALIX, and TSG101, while notably lacking GM130 expression.ConclusionWe successfully isolated primary stem cells from deer antler and established the immortalized hTERT-AnSCs. Remarkably, this cell line maintains its stem cell characteristics even after 40 passages. The sEVs derived from these cells exhibit identical morphological and structural features to those of primary AnSCs. This research provides essential technical support for the application of AnSCs and their sEVs in regenerative medicine.